Identifikasi Perilaku dan Karakter Awal Peserta Didik di SDN Cengklong 3 - Magdalena, Ina; Septianih, Nabilah; Aryanih, Eka; Ayanih, Ayanih (ALSYS, 2022)
This study aims to identify the initial behavior and characteristics of students as a process that must be passed by 5th grade teachers at SDN Cengklong 3 in designing their learning. This study used descriptive qualitative method. Data collection through Observation, Interview, and Documentation. Based on the results of the study, it was found that each student had different characteristics and learning styles. Therefore, every education implementer must be able to know and understand the characteristics of each student so that learning can run smoothly. Teachers can make learning implementation plans with methods and media that can make learning more effective. The various differences in students that educators or teachers need to know are: (1) Characteristics of students, (2) Intelligence of students, and (3) Learning styles.